Getting good help: a guide for reflection, debriefing and feedback conversations about in-consultation supervision. Issue 2 (4th March 2021) - Sturman, Nancy; Fitzmaurice, Liz; Ingham, Gerard; Lee, Cathy; Sheldrake, Michelle
ABSTRACT: Timely supervisor input to the care of their trainees' patients plays a key role in ensuring the safety of patients under the care of general practice trainees. Supervisor responses to trainee calls for assistance are also important for trainee learning and professional identity formation. The in-consultation supervisory encounter in general practice training is, however, a complex social space with multiple trainee, supervisor and patient agendas. Trainee requests for assistance during their consultations are known to present general practitioner supervisors with a number of challenges. From the trainee's perspective, a safe learning environment is essential during these supervisory interactions. A number of factors may act as barriers to, or reduce the usefulness of, in-consultation assistance in particular, resulting in trainees being less likely to seek such assistance on future occasions. It is therefore important to improve both trainee and supervisor skills in safe, effective and efficient in-consultation supervision. Making time for trainee and supervisor conversations about their help-seeking and help provision may uncover opportunities for improving skills, aligning agendas and enhancing outcomes. Finding time for debriefing, reflection and effective feedback conversations may be challenging, however, and opportunities for trainees to provide feedback to their supervisors are known to be particularly limited. We introduce a Debriefing, Reflection and Feedback Guide which is designed to prompt reflection, and structure effective and efficient debriefing and reciprocal feedback conversations. We outline the evidence which informed the development of the Guides, and present some preliminary findings from a pilot in Australian general practice training.